Managing the interior design projects using BIM Technology in Egypt: State of the art - Solaiman Hassan; Amal Abd-El khalee; Doaa Al-Aydi (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
Building Information Modeling (BIM) technology is characterized by providing many accurate information during the project life cycle.This research came to extrapolate the current situation of the use of BIM technology in the field of interior design project management In Egypt, through the use of the Statistical Survey Methodology, which relies on To collect, record and analyze the data obtained through the participation of 50 interior design companies in Egypt in a questionnaire to answer the following questions:What are the types of projects in which technology is used? What are the main reasons why companies use technology? What are the most important software used and the criteria that are relied upon when choosing software when applying BIM technology? What are the most important features and benefits of BIM technology? What are the obstacles that companies face when using technology? What is the importance of BIM during the project life cycle? Which is better, managing interior design projects the traditional way or the BIM technology?By analyzing these answers quantitatively and qualitatively, a set of results was obtained that reflect the current situation of BIM technology in Egypt.In this area.